2020
DOI: 10.3389/fphar.2020.575022
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Clinical Pharmacist-Led Consultation in the Treatment of Infectious Diseases: A Prospective, Multicenter, Cohort Study

Abstract: Background: Antimicrobial resistance (AMR) is a serious global health threat and leads to a huge challenge to infectious diseases (ID) treatment. To tackle AMR, regional 'Antimicrobial Stewardship Programs' (ASP) have been implemented in many countries. Due to insufficient clinical pharmacy resources, a major intervention mode of ASP in China is through clinical pharmacist-led consultation (CPC). The current study aims to prospectively evaluate this intervention and compare the effectiveness of CPC served by I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 34 publications
0
11
0
Order By: Relevance
“…Clinical pharmacist intervention has been shown to be effective in enhancing appropriate use of antibiotics and reducing their toxicity, which may improve patient care. Moreover these had a positive impact not only on the clinical, but on financial outcomes [131][132][133][134][135].…”
Section: Methods Of Reducing the Frequency And Severity Of Antibiotic...mentioning
confidence: 99%
“…Clinical pharmacist intervention has been shown to be effective in enhancing appropriate use of antibiotics and reducing their toxicity, which may improve patient care. Moreover these had a positive impact not only on the clinical, but on financial outcomes [131][132][133][134][135].…”
Section: Methods Of Reducing the Frequency And Severity Of Antibiotic...mentioning
confidence: 99%
“…Similarly, in 222 adult patients hospitalized with Staphylococcus aureus bacteremia, treatment failure at 30 days was independently associated with serum albumin levels (adjusted odds ratio, 0.88; 95% confidence interval, 0.80 to 0.96; p = 0.003) [ 180 ]. A recent prospective cohort study of clinical pharmacist-led antimicrobial treatment consultation in 2663 patients confirmed that hypoalbuminemia is independently associated with a decrease in effective response rate to antimicrobial treatment (adjusted odds ratio, 0.69; 95% confidence interval, 0.52 to 0.92; p = 0.012) [ 186 ].…”
Section: Hypoalbuminemia and Antimicrobial Treatmentmentioning
confidence: 99%
“…In terms of this primary endpoint, we would have addressed ERC as the minimal response rate (MRR). However, when searching for relevant literature, we found that in the studies of Zhang JX et al 5,56 on the effectiveness of clinical pharmacists’ consultations, the primary endpoint was effective response (complete or partial response). The endpoint was defined as partial or complete resolution of clinically significant signs/symptom improvement or resolution of computed tomography (CT) or magnetic resonance imaging (MRI) findings and on proven or negative culture results.…”
Section: Discussionmentioning
confidence: 99%